Clinicopathologic Features of Primary Merkel Cell Carcinoma: A Detailed Descriptive Analysis of a Large Contemporary Cohort. Issue 7 (3rd April 2013) - Schwartz, Jennifer L.; Bichakjian, Christopher K.; Lowe, Lori; Griffith, Kent A.; Frohm, Marcus L.; Fullen, Douglas R.; Hayman, James A.; Lao, Christopher D.; Shah, Khooshbu S.; McLean, Scott A.; Bradford, Carol R.; Johnson, Timothy M.; et al.
<x xml:space="preserve">Abstract</x> Background Little uniformity exists in the clinical and histologic variables reported with primary Merkel cell carcinoma (MCC). Objective To provide a rigorous descriptive analysis of a contemporary cohort and promote the prospective collection of detailed data on MCC for future outcome studies. Methods and Materials A detailed descriptive analysis was performed for clinical and histologic features of 147 patients with 150 primary MCC tumors in a prospectively collected database from 2006 to 2010. Results The majority (73.5%) of patients were at American Joint Committee on Cancer clinical stage I or II at presentation, 20.4% at stage III, and 6.1% at stage IV. Detailed descriptive clinical and histologic findings are presented. Conclusion Clinical and histologic profiling of primary MCC in the literature is variable and limited. Systematic prospective collection of MCC data is needed for future outcome studies and the ability to compare and share data from multiple sources for this relatively rare tumor.